ANALISIS PEMANFAATAN RUANG TANAMAN KELAPA BERDASARKAN KESESUAIAN LAHAN FISIK DAN EKONOMI: Study Kasus di Kabupaten Sidenreng Rappang, Sulawesi Selatan - -, Haikal (Jurnal Ilmiah Ecosystem, 2016)
This study aims to determine the physical land suitability classes, and the economy and determine the feasibility of the coconut crop farming. Data analysis using Automated Land Evaluation System (ALES) to determine the suitability of land economy class.The results showed that the physical land suitability classes in all the land units are the major limiting factor rooting conditions, with details on land units 1 and 4 sub-class S2r with descriptions rather according to the constraint condition of rooting texture dusty clay and clay loam; 2 sub-class land units S3R and S2r with a description of the dominant accordance marginal marginal and somewhat accordance with the constraints of rooting conditions argillaceous sand texture and texture modifier being; land units 5 and 6 sub-class S3R with the description in accordance with the constraints marginal rooting conditions: 45 cm into the ground effectively and sandy loam texture; 3 land units have a sub-class S3R and N with a description of the dominant accordance marginal and not in accordance with the constraints of rooting conditions: effective depth of 35 cm soil and sandy loam soil texture.While compliance economic land for cocoa plants by class kesesuaiam land physically above then consider the factors supporting and inhibiting factors in the respective land units, using the Automated Land Evaluation System, the result is that land units 1, 2 and 4, the value of land suitability rather favorably with the minimum limit profit between Rp.1.000.000,00, - up to Rp.8.000.000,00, - / ha / year, land Unit 3, 5 and 6 the conformity of marginal land profitable with a minimum limit of <Rp.1.000.000,00 , -